Recompression chamber, its relationship with the hyperbaric chamber - Guicheff, Vladimir (Cirugía del Uruguay, 2021)
The recompression chamber is no more and no less than a hyperbaric chamber which is serving a different purpose. But it does not differ from the latter in the least, either in its fundamental principle or in the material of which it is made. Therefore we hope that in the future we may get a chamber for the use of hyperbaric 02 built in an adequate place and thus we shall be able to add a new weapon to the therapeutic arsenal in the fight against the different diseases for which this type of therapeutics can be employed.